Statistical optimization of aeration and agitation for sewage treatment plant sludge treatment in stirred tank bioreactor - Alam, Md. Zahangir; Muyibi, Suleyman Aremu; Jamal, Parveen; Khan Chowdhury, Ahmed Jalal (2006)
A 2-level full factorial design (22) with one central point was employed to determine the optimum agitation and aeration for effective bioconversion of STP sludge by pure bacterial culture through the removal of chemical oxygen demand (COD). A second order polynomial model was developed to determine the removal of COD with the variation of process conditions in the sludge treatment. Analysis of variance (ANOVA) of full factorial design showed a high coefficient of determination (R2) of 0.976 indicating a satisfactory adjustment of the model with the experimental data. The linear and interaction effects among the factors were identified through the p- and t-test for both cases. The results with the surface response analysis indicated the optimum values of parameters in stirred tank bioreactor were aeration of 1 vvm and agitation of 50 rpm. The final removal of COD with optimum conditions was observed to be 39 mg/L which validated the model determined.